Poverty Analysis in Indonesia’s Ten Poorest Provinces: Socio-economic and Fiscal Determinants - Mailyn, Frisilia Dameria; Kartika, Metasari (Department of Economics, Faculty of Economics and Business, Universitas Airlangga, 2025)
Objective: As a developing country, Indonesia is still economically vulnerable. This study analyzes the influence of health complaints, school participation rate, per capita expenditure, General Allocation Fund, Special Allocation Fund, and open unemployment rate on poverty. Grounded in the Human Capital, Keynesian, Fiscal Federalism, and Malthusian Theory, the empirical study explains the socioeconomic and fiscal dimensions of poverty to evaluate the policy effectiveness in Indonesia. Design/Methods/Approach: This study employs panel data (2014-2023) from Statistics Indonesia and the Ministry of Finance, covering the ten poorest provinces. Multiple linear regression is the method employed by EViews 12 under a Random Effects model, because provincial differences are assumed to be random and uncorrelated with the independent variables. Findings: The results reveal that health complaints have a negative but insignificant effect on poverty. School participation rate and per capita expenditure significantly reduce poverty depth, reflecting the roles of human capital accumulation and household purchasing power in improving welfare. The General Allocation Fund exhibits a positive but insignificant effect, whereas the Special Allocation Fund significantly increases poverty, indicating misallocation and inefficiencies in fiscal implementation. The open unemployment rate has a positive and significant effect, as loss of income pushes households further below the poverty line. Originality/Value: This study offers novel value by focusing specifically on the ten provinces with the highest poverty depth, which is rarely examined in prior research. The study provides evidence that the determinants of poverty are not universal but vary across regional contexts. The findings extend existing literature by highlighting the role of fiscal governance quality, particularly the divergent effects of transfer funds. Practical/Policy implication: These findings provide strategies for poverty alleviation in the poorest regions, such as expanding equitable access to health and education services, strengthening employment programs, and improving the transparency and targeting of fiscal transfers.